KAJIAN ESTETIKA MASJID SALMAN ITB DITINJAU DARI STRUKTUR - Gilang Pratomo; Kamal Abdullah Arif; Enrico Nirwan Histanto (Riset Arsitektur (RISA), 2023)
Abstract - The Salman ITB Mosque is one of Indonesia's most important architectural accomplishments. It has an upward curved roof with a column-free prayer space that is still in good working order. The structure serves as a medium for distributing load, but the structural function of a building extends beyond that to include the aesthetic value of the architectural work itself. The purpose of this study is to look at the use of structures in the Salman ITB Mosque building, which not only serve as a means of distributing loads but also have an aesthetic value. The findings of the study could lead to scientific advancements in the construction of structures that improve the aesthetic value of structures. Designers can use this knowledge to create structure-based designs in the future, so that structural aspects are no longer considered as an afterthought to the architectural design, but are valued equally. The Bjorn Normann hypothesis is used to investigate the structure's aesthetics, which states that the structure's aesthetics can be appraised based on its structural and architectural functions. The outcomes of the study of books connected to structure will be based on the theory. This is a qualitative descriptive study that uses data from book reviews, direct observation, interviews, and simulations to process the data. The analysis is split into two sections. The first section is devoted to a consideration of the structure and its structural features as a load-distribution medium. The second section delves into the structure's architectural features, such as forms, expressions, and elements that divide the space. Findings emerged from the conversation, which were used to draw conclusions. The structure, as a space-forming element, plays the most important role in accomplishing structural ethics at the Salman Mosque ITB, according to this study. Furthermore, in the ITB Salman Mosque, the structure as an expression of the building still plays a significant part in achieving the structure's aesthetics. Finally, in the Salman ITB Mosque, the structure as a type of building plays the least important function in achieving structural beauty. This is possible due to the structure's position as a load distributor, which places a premium on optimizing the structure's design and arrangement. Keywords: Salman Mosque ITB, structural aesthetics, structural function, architectural functions, load distribution, form, expression, and interior space.